Volume 5B: Heat Transfer 2019
DOI: 10.1115/gt2019-91848
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature Distribution on Radial Growth of Compressor Discs

Abstract: For the next generation of aero-engines, manufacturers are planning to increase the overall compressor pressure ratio from existing values around 50:1 to values of 70:1. The requirement to control the tight clearances between the blade tips and the casing over all engine-operating conditions is a challenge for the engine designer attempting to minimise tip-clearances losses. Accurate prediction of the tip clearance requires an accurate prediction of the radial growth of the compressor rotor, which depends on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Long and Childs [22] employed Lloyd and Moran's [27] correlation to scale their heat transfer measurements, using a Nusselt number based on the core-to-shroud temperature difference. The modified 1 Rayleigh number Ra and the modified Nusselt number Nu are given in Eqs. (15) and (16).…”
Section: Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Long and Childs [22] employed Lloyd and Moran's [27] correlation to scale their heat transfer measurements, using a Nusselt number based on the core-to-shroud temperature difference. The modified 1 Rayleigh number Ra and the modified Nusselt number Nu are given in Eqs. (15) and (16).…”
Section: Heat Transfermentioning
confidence: 99%
“…Without corresponding reductions in blade tip-to-casing clearance this will result in a larger blade tip clearance-to-blade span ratio, which will in turn lead to proportionally higher tip clearance losses. The blade tip clearance of the last axial compressor stage at near nominal engine speed is of the same order of magnitude as the thermal and centrifugal growths of the compressor rotor disc [1]. The thermal growth is determined by the thermal stresses on the discs characterised by the disc temperature distribution, which is associated with the flow and heat transfer in the rotating compressor disc cavities.…”
Section: Introductionmentioning
confidence: 99%
“…This review was extended by Luberti et al [2], including discussion of the most recent and relevant experimental work from the universities at Sussex [3], Dresden [4,5] and Beihang [6]. Luberti et al [7] showed that the radial distribution of temperature has a significant effect on the disc growth and consequently on the blade clearance in a compressor. Although the growth due to the thermal stress is small relative to the total growth of the disc, it is the same magnitude as the blade clearance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Long and Childs [22] employed Lloyd and Moran's [27] correlation to scale their heat transfer measurements, using a Nusselt number based on the core-to-shroud temperature difference. The modified 1 Rayleigh number Ra and the modified Nusselt number Nu are given in Eqs. ( 15) and ( 16).…”
Section: Heat Transfermentioning
confidence: 99%